Emission-based interest rates and the transition to a low-carbon economy - Florian Böser; Chiara Colesanti Senni (ETH Zurich, CER-ETH - Center of Economic Research, 2020)
We use a dynamic general equilibrium model to study a climate-oriented monetary policy in the form of emission-based interest rates set by the central bank. Liquidity costs of banks increase with the emission intensity of their asset portfolio, leading banks to favor low-carbon assets and to improve the financing conditions for clean sectors. We show that such a monetary policy supports the decarbonization of the economy and reduces climate damage, as more resources are channeled to low-carbon sectors and incentives to adopt cleaner technologies increase across all sectors. We illustrate these effects by calibrating our model to data for the Euro Area.
Keywords: E42; E52; E58; O44; 330; climate change; monetary policy; banks; innovation; financial stability